2017
DOI: 10.1177/0192623316672075
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in Types and Incidence of Neoplasms in Wistar Han and Sprague-Dawley Rats

Abstract: A substantial quantity of data on Sprague-Dawley (SD) and Hannover Wistar rats strains have been published concerning their source, diet, and housing conditions, as well as the incidences of nonneoplastic lesions and neoplasms observed in different laboratories. Differences between the commonly used rat strains provided by different breeders (i.e., CD (SD) vs. Harlan Sprague-Dawley strain or Crl: WI(Han) vs. Wistar Hannover (Han)-derived strain, continued breeding by RCC Ltd., Switzerland, thereafter continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
10
21
0
3
Order By: Relevance
“…A large amount of histopathological data has been published on the three main strains of rat used in carcinogenicity studies, i.e. Wistar Han, Sprague-Dawley, and Fischer 344 (Weber 2017). It is well known that Fischer 344 rats are prone to develop spontaneous myeloid leukemia and Leydig cell tumours, while Sprague-Dawley rats show high incidence rates in the case of spontaneous pituitary gland adenomas and mammary gland neoplasms (Weber 2017).…”
Section: Rat Feeding Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large amount of histopathological data has been published on the three main strains of rat used in carcinogenicity studies, i.e. Wistar Han, Sprague-Dawley, and Fischer 344 (Weber 2017). It is well known that Fischer 344 rats are prone to develop spontaneous myeloid leukemia and Leydig cell tumours, while Sprague-Dawley rats show high incidence rates in the case of spontaneous pituitary gland adenomas and mammary gland neoplasms (Weber 2017).…”
Section: Rat Feeding Trialsmentioning
confidence: 99%
“…Wistar Han, Sprague-Dawley, and Fischer 344 (Weber 2017). It is well known that Fischer 344 rats are prone to develop spontaneous myeloid leukemia and Leydig cell tumours, while Sprague-Dawley rats show high incidence rates in the case of spontaneous pituitary gland adenomas and mammary gland neoplasms (Weber 2017). The Wistar Han rat strain was used to perform the three feeding trials described in this paper because it shows the lowest incidence of spontaneous tumours in most organs when compared to the Fischer 344 and Sprague-Dawley strains.…”
Section: Rat Feeding Trialsmentioning
confidence: 99%
“…Although not considered a common spontaneous lesion in rats, incidences of Zymbal's gland tumors in control animals of toxicological studies have been identified (Dinse, Peddada, Harris, & Elmore, 2010;Rudmann et al, 2012;Weber, 2017 Thompson et al, 2005). Increases in spontaneous mutations resulting from the presence of free amino acids in the medium can be misinterpreted as a substance-related genotoxic response when in fact it is the amino acid content of the culture medium that is responsible for the overall increase in the bacterial growth and greater potential for mutations to occur.…”
Section: In Vivo Comet Testmentioning
confidence: 99%
“…Although not considered a common spontaneous lesion in rats, incidences of Zymbal's gland tumors in control animals of toxicological studies have been identified (Dinse, Peddada, Harris, & Elmore, 2010;Rudmann et al, 2012;Weber, 2017 Following exposure to AG concentrate, significant increases in revertant colonies (twofold or greater) were observed in S. typhimurium strains TA100 and TA1535 in the presence and absence of metabolic activation and in TA98 and TA1537 in the absence of metabolic activation when tested in initial preliminary and dose-finding bacterial reverse mutation studies under the conditions of the preincubation method. A similar increase in the number of revertants also was observed in the main study with TA98 tested with metabolic activation under preincubation conditions.…”
Section: In Vivo Comet Testmentioning
confidence: 99%
“…RccHan:WIST, a Wistar substrain, has been recently available in Europe, the US, and Japan. Envigo (Huntingdon, UK) has provided background data for this strain, showing that there are differences in the incidence or severity of some neoplasms or toxicologically important lesions 1,2 . In Japan, several pathologists have reported on the characteristics and biochemical parameters of RccHan:WIST rats 3 , as well as spontaneous lesions that have occurred in the cornea 4 and the uterine horn 5 .…”
mentioning
confidence: 99%